THE ROLE OF COMPUTER IN DESKTOP PUBLISHING - Tjuk Indarsih; Djoko Harmanto, MS (Jurnal Sistem Informasi, 1989)
The birth of the term desktop publishing due to the increasing use of computers in thebusiness world. This term appears in the print world, where its presence raises aquestion for those concerned as to whether it was desktop publishing, and for what.On the other hand the emergence of this term is a new opportunity for a variety ofcomputers and devices that can be offered with menyandak predicate. In thesecircumstances, of course the information is required, let alone computers aregenerally still regarded as new products in the world of printing.